On the Gain of NOMA in Wireless Powered Networks with Circuit Power Consumption - Vranas, Christos K.; Bouzinis, Pavlos S.; Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (IEEE Communications Letters, 2019)
This letter investigates when non-orthogonal multiple access (NOMA) outperforms time-division multiple access (TDMA) for use in the uplink of wireless powered networks, assuming non-negligible circuit power consumption and a non-linear energy harvesting model. To this end, we propose a resource allocation scheme that maximizes the minimum rate among the users, by optimizing the allocated time to energy harvesting and information transmission. The formulated problem is optimally and efficiently solved by using a novel algorithm, which is based on the derived analytical expressions and the bisection method. The simulations results show that NOMA is superior to TDMA for practical values of circuit power consumption.
Created from Fastlane, Scopus look-up
Keywords: circuit power consumption; non linear energy harvesting model; Non-orthogonal multiple access (NOMA); wireless powered networks (WPNs)